1983
DOI: 10.1111/j.1476-5381.1983.tb11051.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhibition of synthesis and receptor antagonism of SRS‐ A in cardiac anaphylaxis

Abstract: 1 The effects of infusions of the lipoxygenase inhibitor nordihydroguaiaretic acid (NDGA, 1.1 x 10-molmin-') and the antagonist of slow-reacting substance of anaphylaxis (SRS-A) FPL 55712 (1.2 x 10-mol min-') on the coronary constriction and the release of SRS-A, leukotriene C4-like immunoreactivity, thromboxane B2 and 6-keto-prostaglandin Fl. from perfused anaphylactic guinea-pig hearts were investigated. 2 Both NDGA and FPL 55712 in the concentrations used induced an increase in basal coronary flow, but did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…USA 84 (1987) 0 anaphylaxis (11)(12)(13)(14). It has also been documented that inhibitors of leukotriene formation can prevent several anaphylactic responses (29)(30)(31) …”
Section: %1mentioning
confidence: 99%
“…USA 84 (1987) 0 anaphylaxis (11)(12)(13)(14). It has also been documented that inhibitors of leukotriene formation can prevent several anaphylactic responses (29)(30)(31) …”
Section: %1mentioning
confidence: 99%
“…In addition, electrocardiographic changes have been found that are similar to those observed in man during anaphylaxis (Capurro & Levi, 1975). Furthermore, upon immunological challenge, various mediators, which could be responsible for the observed changes in cardiac function, like histamine (Brocklehurst, 1960;Feigen & Prager, 1969) slowreacting substance of anaphylaxis (SRS-A) (Brocklehurst, 1960;Liebig et al, 1975) or sulphidopeptideleukotrienes (SP-LT) (Aehringhaus et al, 1983), platelet-activating factor (Paf-acether) , prostaglandins (Liebig et al, 1975;Levi et al, 1976;Anhut et al, 1978;Peskar et al, 1979;Allan & Levi, 1981), and thromboxane B2 (TXB2) (Anhut et al, 1977;Allan & Levi, 1981), the stable degradation product of the biologically active TXA2, have been detected in perfusates of anaphylactic guinea-pig hearts.…”
Section: Introductionmentioning
confidence: 71%
“…In fact the validity of the method in this particular system has been repeatedly checked by correlation to bioassay data (Aehringhaus et al, 1983). Relative cross-reaction of LTC, with the anti SP-LT antiserum was 99%.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations